Clinical significance of signs of autoimmune colitis in 18F-fluorodeoxyglucose positron emission tomography-computed tomography of 100 stage-IV melanoma patients - Lang, Nina; Dick, Julika; Slynko, Alla; Schulz, Carsten; Dimitrakopoulou-Strauss, Antonia; Sachpekidis, Christos; Enk, Alexander; Hassel, Jessica C. (Immunotherapy, 2019)
Aim: Autoimmune colitis is a typical and possible severe side effect among patients treated with ipilimumab. Patients & methods: We prospectively included 100 patients with metastasized melanoma under ipilimumab treatment in a radiological study of 18F-fluorodeoxyglucose positron emission tomography-computed tomography (18F-FDG PET-CT). PET evidence of pancolitis ('PET-colitis') was correlated with clinical variables. Results: We observed a significant correlation between PET-colitis and clinically significant diarrhoea, although PET-colitis was more frequent (49 vs 29% of patients, respectively). Neither PET-colitis nor diarrhoea was significantly correlated with response to therapy. Other immune-related adverse events, however, such as hypophysitis and hepatitis were associated with response to therapy and overall survival. Conclusion: Increased 18F-FDG uptake in the colon correlated with clinical symptoms but did not predict clinical outcome to ipilimumab.
Gesehen am 13.08.2019
Im Titel ist die Zahl "18" hochgestellt